Studi Kecelakaan Lalu Lintas (Pada Ruas Jalan Yogyakarta - Wates Km 19 s/d Km 22) - Marlina (Jurusan T.Sipil Fakultas Tekni UMY, 2012)
Studi Kecelakaan Lalu Lintas (Pada Ruas Jalan Yogyakarta - Wates Km 19 s/d Km 22)